MENAKAR KOHERENSI TATA KELOLA PERUBAHAN IKLIM ATAS HAK MASYARAKAT ADAT DALAM PROGRAM PERDAGANGAN KARBON DI KALIMANTAN TIMUR - Khoirul Amin; Devy Indah Paramitha; Mohamad Dziqie Aulia Al Farauqi (Jurnal Dinamika Global, 2024)
As part of climate change mitigation efforts and Indonesia's commitment to realizing low-emission land-based development, the Indonesian government through the Ministry of Environment and Forestry (KLHK) and the World Bank are following up on the REDD+ agenda through the Forest Carbon Partnership Facility (FCPF). The agreement aims to provide full support for increasing Indonesia's capacity in formulating a national strategy in realizing reduced emissions from deforestation and forest degradation. East Kalimantan Province is the selected region to follow the emission reduction target. The target set is to reduce emissions by 41% in 2030. In its development, the framework has entered the implementation phase and results-based payments. However, the distribution of incentives from selling carbon to Indigenous peoples as parties who have rights to carbon and are involved in forest management initiatives has not benefited directly. This research aims to analyze further how the realization of profit sharing and fulfillment of Indigenous peoples' rights over forest management in the FCPF project is a form of coherence in climate change governance towards Indigenous peoples' rights in a fair manner. Using a descriptive qualitative approach, data collection was triangulated through interviews and literature for further reduction and conclusions drawn. The results of this research state that the lack of inclusion of Indigenous communities in an inclusive and participatory manner in the carbon trading framework has the potential to reduce the rights of Indigenous communities to decentralized forest management and their welfare in carbon trading projects.